2017
DOI: 10.7150/thno.19172
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Profiling of Brain Tumors and Cells

Abstract: This study reports vibration profiles of neuronal cells and tissues as well as brain tumor and neocortical specimens. A contact-free method and analysis protocol was designed to convert an atomic force microscope into an ultra-sensitive microphone with capacity to record and listen to live biological samples. A frequency of 3.4 Hz was observed for both cultured rat hippocampal neurons and tissues and vibration could be modulated pharmacologically. Malignant astrocytoma tissue samples obtained from operating ro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 69 publications
0
19
0
Order By: Relevance
“…The distinct mechanical behaviors of classical cadherins and clustered protocadherins predicted by our simulations might also have implications for assembly and differential survival of the junctions they form in various types of tissues. Tissues and individual cell membranes do experience oscillatory motions (145)(146)(147)(148)(149), with amplitudes of up to 3 nm and characteristic timescales that can be slow (hundreds of milliseconds) (149) or fast (hundreds of microseconds) (145). These observations suggest that the junctions we simulated would be subject to periodic stretching and compression.…”
Section: Discussionmentioning
confidence: 80%
“…The distinct mechanical behaviors of classical cadherins and clustered protocadherins predicted by our simulations might also have implications for assembly and differential survival of the junctions they form in various types of tissues. Tissues and individual cell membranes do experience oscillatory motions (145)(146)(147)(148)(149), with amplitudes of up to 3 nm and characteristic timescales that can be slow (hundreds of milliseconds) (149) or fast (hundreds of microseconds) (145). These observations suggest that the junctions we simulated would be subject to periodic stretching and compression.…”
Section: Discussionmentioning
confidence: 80%
“…This might be important in the context of cell oscillations or small-scale tissue stretching (118)(119)(120)(121)(122), where classical cadherin bonds would act as molecular shock absorbers and be mechanically robust, while In turn, the larger interface achieved through overlap by PCDH proteins permits greater variation in the number and type of residues involved in the binding interface, a key determinant of strict homophilic specificity observed for clustered PCDH proteins. These observations suggest that each set of cadherins has evolved to adopt various features (13,(124)(125)(126) 1).…”
Section: Discussionmentioning
confidence: 99%
“…There is substantial potential for misinterpretation of data due to cell damage during the adhesion process [ 163 ]. Studies have demonstrated the effect of bacterial adhesion position distribution on the cantilever, and the effects increased when the adhesion positions were close to the cantilever’s free end [ 164 ]. The cantilever vibration due to the attached bacteria was caused not only by the mass effect but also by the bacterial cells’ stiffness.…”
Section: The Afm Oscillating Sensor Mode (Nanomotion)mentioning
confidence: 99%
“…Nanomotion’s ability to distinguish between living samples based on their propensity to adhere to a surface opens up a wide field of other applications that enable fingerprinting of different living samples according to their health status. Nanomotion was utilized to collect brain tumor vibration signals from cultured cells based on their vibration, allowing for the differentiation of various brain tumors from the normal brain based on nanomotion characteristics [ 164 ].…”
Section: The Afm Oscillating Sensor Mode (Nanomotion)mentioning
confidence: 99%
See 1 more Smart Citation